Systematic review of the effectiveness of arts therapy for children and adolescents with post-traumatic stress disorder - Li, Zehui; Cui, Qiaoyu; Liu, Xinyu (Frontiers in Psychiatry, 2025)
BackgroundArts therapy has gained increasing popularity for alleviating post-traumatic stress disorder (PTSD) in adolescents and children due to its non-intrusive nature and ease of interaction with participants. In this pre-registered systematic review (PROSPERO: 420251060744), we synthesized existing literature on arts therapies as interventions for managing PTSD symptoms in adolescents and children.MethodsWe conducted systematic searches of APA PsycNET, PubMed, EMBASE, Cochrane Library, and Web of Science up to June 15th 2025.Results1,273 articles were identified through systematic searches, with 10 articles meeting our inclusion criteria. These studies reported some positive outcomes from visual art therapy, music therapy, dance therapy, drama therapy, and poetry therapy; however, the effectiveness of individual arts therapies in improving PTSD symptoms was inconclusive.ConclusionArts therapies demonstrate significant effects on certain symptoms of children and adolescents with PTSD. However, more rigorous studies are warranted to substantiate the efficacy and generalizability of arts therapies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251060744.